2011
DOI: 10.1007/s13365-010-0014-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of co-selected single nucleotide polymorphisms in the viral promoter precedes the onset of human immunodeficiency virus type 1-associated neurocognitive impairment

Abstract: The long terminal repeat (LTR) regulates gene expression of HIV-1 by interacting with multiple host and viral factors. Cross-sectional studies in the pre-HAART era demonstrated that single nucleotide polymorphisms (SNPs) in peripheral blood-derived LTRs (a C-to-T change at position 3 of C/EBP site I (3T) and at position 5 of Sp site III (5T)) increased in frequency as disease severity increased. Additionally, the 3T variant correlated with HIV-1-associated dementia. LTR sequences derived by longitudinal sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 35 publications
0
56
0
Order By: Relevance
“…22 The study was approved by the Drexel University College of Medicine Institutional Review Board under protocol 16311 (Brian Wigdahl, principal investigator) in compliance with Helsinki Declaration of 1975 as revised in 2000. All participants were required to provide informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The study was approved by the Drexel University College of Medicine Institutional Review Board under protocol 16311 (Brian Wigdahl, principal investigator) in compliance with Helsinki Declaration of 1975 as revised in 2000. All participants were required to provide informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Once a subject was enrolled, an anonymous identifier was assigned and the patient's clinical data were collected as previously described. 22 Blood samples were drawn from each patient at the initial visit and at each return visit (approximately every 6 months but at least one recall per year) to allow for longitudinal study. Patients were considered preferential nonusers (PN) if they tested negative for all drugs at all visits and never admitted to drug use.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in the Drexel Medicine CARES Cohort have been recruited from the Partnership Comprehensive Care Practice of the Division of Infectious Disease and HIV Medicine at Drexel University College of Medicine, which is located in Center City Philadelphia, Pennsylvania, USA as previously described [32]. The study was approved by the Drexel University College of Medicine Institutional Review Board under protocol 1201000748 (Brian Wigdahl, principal investigator) in compliance with Helsinki Declaration of 1975 as revised in 2000.…”
Section: Patient Recruitment Clinical Data and Sample Collectionmentioning
confidence: 99%
“…However, one must remember that these viral gene activation studies were performed with a viral regulatory region that was derived from a non-CNS tissue source and may, therefore, not be naturally compatible with respect to optimal LTR activation by a Tat protein selected for CNS replication. This is particularly important because previous studies (Burdo, Gartner, Mauger, & Wigdahl, 2004; Hogan, Nonnemacher, Krebs, Henderson, & Wigdahl, 2003; Hogan, Stauff, et al, 2003) demonstrated that LTRs derived from the CNS are likely to be structurally and functionally different from LTRs derived from other tissue sources and that colinear Tat and LTR combinations may result in more efficient LTR activation (Li et al, 2011). Nonetheless, taken together, these reports suggest that genetic diversity of HIV-1 Tat very likely contributes to the establishment and severity of HAND.…”
Section: Genetic Diversity Within Hiv-1 Tat Vpr and The Ltr Andmentioning
confidence: 99%